Practical tips on counseling pregnant women with group B Streptococcus infection - A.A. Pashchenko; L.S. Dzhokhadze; Yu.E. Dobrokhotova; T.S. Kotomina; A.N. Efremov (LCC «Medicine-Inform», 2022)
A.A. Pashchenko1, L.S. Dzhokhadze1, Yu.E. Dobrokhotova1, T.S. Kotomina2, A.N. Efremov2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Branch of the City Clinical Hospital No. 52, Moscow, Russian Federation Interpretation of smears identified group B Streptococcus (S. agalactiae) in various titers in urogenital epithelium depending on gestation term and management of pregnant women requiring antibiotics are still disputable among inpatient and outpatient obstetricians and gynecologists. It was demonstrated that S. agalactiae persistence in pregnant women without timely antibacterial therapy during delivery to eliminate microbes is reliably associated with severe infectious complications in the early neonatal period (e.g., newborn meningitis or sepsis). This paper systematically reviews recent publications and analyzes current clinical guidelines of global professional medical associations on the colonization of the urogenital tract of pregnant women with group B Streptococcus. The authors provide recommendations on managing pregnant women with S. agalactiae infection depending on gestation terms and microbial count to improve the diagnosis and medical treatment algorithms. Principles of rational pharmacotherapy in these pregnant women (including those in the intranatal period) are addressed. Keywords: group B streptococcus, S. agalactia, GBS colonization, systematic review, asymptomatic bacteriuria, rational pharmacotherapy, pregnant women. For citation: Pashchenko A.A., Dzhokhadze L.S., Dobrokhotova Yu.E. et al. Practical tips on counseling pregnant women with group B Streptococcus infection. Russian Journal of Woman and Child Health. 2022;5(1):51-57 (in Russ.). DOI: 10.32364/2618-8430-2022-5-1-51-57.